Perceived Pain in Athletes: A Comparison between Endurance Runners and Powerlifters through a Cold Experimental Stimulation and Two Sessions of Various Physical Activation - Pierluigi Diotaiuti; Angelo Rodio; Stefano Corrado; Stefania Mancone; Fernando Bellizzi; Thais Cristina Siqueira; Alexandro Andrade (MDPI AG, 2022)
Few studies in the literature have illustrated cold hypoalgesia induced by strength training. Objectives of this contribution were to compare the ratings of perceived pain in endurance running (n = 22) and powerlifting (n = 22) male athletes and controls (n = 22) at baseline and after two bouts of 40 min aerobic/strength training respectively, using the Cold Pressor Test (CPT) and simultaneously monitoring changes in blood pressure (BP), heart rate (HR), and body temperature. A two-way repeated measures ANOVA was conducted to examine the effects of training sessions in endurance runners vs. powerlifting athletes vs. controls on the intensity of perceived pain at CPT. A statistically significant two-way interaction between the group and training resulted in p < 0.001, ηp2 = 0.513. A simple main effects analysis showed that as the participants went through the strength training session, pain perception at CPT was significantly lower in powerlifters compared to runners and controls. Considering the physiological parameters, powerlifters reported significantly higher values of BP and HR. This difference was present at baseline but after training as well, and before and after CPT, despite a slight hypotensive effect. The differences reported after CPT at baseline, but very significantly after the strength activation session in the powerlifters, provide interesting insights into the hypoalgesic effect of high-intensity strength training.